2020
DOI: 10.3390/ijerph17207380
|View full text |Cite
|
Sign up to set email alerts
|

Responders to Exercise Therapy in Patients with Osteoarthritis of the Hip: A Systematic Review and Meta-Analysis

Abstract: The Outcome Measures in Rheumatology workgroup (OMERACT), together with the Osteoarthritis Research Society International (OARSI) developed the OMERACT-OARSI responder criteria. These criteria are used to determine if a patient with osteoarthritis (OA) ‘responds’ to therapy, meaning experiences a clinically relevant effect of therapy. Recently, more clinical OA trials report on this outcome and most OA trials have data to calculate the number of responders according to these criteria. A systematic review and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Although systematic reviews suggest, on average, small-to-moderate effects on pain, physical function, and quality of life, several studies have shown marked differences in individual patients’ treatment response [ 54 , 56 , 57 ]. However, recent efforts to identify potential treatment response moderators (i.e., characteristics that might impact patient response) of the effect of exercise therapy for knee OA have produced inconclusive or conflicting results.…”
Section: Which Patients Do and Do Not Benefit From Exercise?mentioning
confidence: 99%
“…Although systematic reviews suggest, on average, small-to-moderate effects on pain, physical function, and quality of life, several studies have shown marked differences in individual patients’ treatment response [ 54 , 56 , 57 ]. However, recent efforts to identify potential treatment response moderators (i.e., characteristics that might impact patient response) of the effect of exercise therapy for knee OA have produced inconclusive or conflicting results.…”
Section: Which Patients Do and Do Not Benefit From Exercise?mentioning
confidence: 99%
“…The of OMERACT-OARSI responders in previous research of OA management varies widely. The proportion of responders varies from 25% to 83%, [36][37][38] hence, a conservative estimate in our trial would be 50% being classified as responders. No direct comparison of our study to other trials is to our knowledge available, increasing difficulty of specifying a non-inferior margin.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…1 3 The common finding of relatively small treatment effects for many interventions has nourished the belief that subgroups showing larger effects may be identified in more homogenous groups of patients. [4][5][6] This belief has driven the interest in identifying subgroups of patients likely to respond better to specific interventions or respond poorly to an intervention where other approaches may be more efficacious. 7 A well-recognised method for identifying clinically relevant subgroups in a patient population is to analyse treatment effect modifiers using randomised controlled trial (RCT) data.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical guidelines universally recommend patient education and exercise therapy as first-line treatments for knee and hip osteoarthritis (OA)1–3 complemented by weight loss, non-steroidal anti-inflammatory drugs, corticosteroids or hyaluronic acid injections, and several adjunctive medications and interventions 1 3. The common finding of relatively small treatment effects for many interventions has nourished the belief that subgroups showing larger effects may be identified in more homogenous groups of patients 4–6. This belief has driven the interest in identifying subgroups of patients likely to respond better to specific interventions or respond poorly to an intervention where other approaches may be more efficacious 7…”
Section: Introductionmentioning
confidence: 99%